Integration of Ecotheology In Tasks And Functions Religious Extension Workers on The Issue of Environmental Crisis in the North Minahasa - Alfian Revel Sumilat (International Journal of Education, Information Technology, and Others, 2026)
The environmental crisis in Indonesia is increasingly impacting the welfare of local communities, including in North Minahasa Regency which is experiencing pressure from coastal development, increasing domestic waste, and degradation of marine ecosystems. This problem is not only ecological, but also moral and social, so it requires an approach that touches on changing public consciousness. This research aims to analyze the integration of ecotheology in the duties and functions of religious extension workers as a social transformation strategy in responding to environmental crises. The research uses an interpretive qualitative approach through a systematic literature review and analysis of the socio-ecological context of the region. The data were analyzed thematically reflective with reinforcement of social change theory, critical education, and transformative learning. The results of the study show that the integration of ecotheological values in religious counseling is able to form ecological moral awareness, encourage environmentally friendly behavior change, and strengthen community social solidarity. Counseling not only serves as spiritual education, but also as a space for faith practice through collective action such as waste management, coastal care, and cross-generational environmental education. This integration gives birth to a sustainable and contextual faith-based ecological culture. This research confirms that religious extension workers have a strategic role as agents of socio-ecological transformation, as well as that ecotheology can be the foundation of public ethics in dealing with environmental crises holistically and equitablely.